2013
DOI: 10.1002/jhm.2093
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in inpatient‐based versus outpatient‐based physicians: A systematic review and meta‐analysis

Abstract: BACKGROUND Burnout is a syndrome affecting the entirety of work life and characterized by cynicism, detachment, and inefficacy. Despite longstanding concerns about burnout in hospital medicine, few data about burnout in hospitalists have been published. PURPOSE A systematic review of the literature on burnout in inpatient‐based and outpatient‐based physicians worldwide was undertaken to determine whether inpatient physicians experience more burnout than outpatient physicians. DATA SOURCES Five medical database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 75 publications
4
25
2
1
Order By: Relevance
“…Burnout has been demonstrated to affect a sizable proportion of hospitalists, with prevalence estimates from prior studies varying from 12.9% to 27.2%, although nearly all studies of US hospitalists have relied on single‐item instruments . Hospital‐based physicians have represented a rapidly expanding segment of the internist workforce for more than a decade, but studies of the impact of inpatient vs outpatient practice location on burnout and career satisfaction are limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Burnout has been demonstrated to affect a sizable proportion of hospitalists, with prevalence estimates from prior studies varying from 12.9% to 27.2%, although nearly all studies of US hospitalists have relied on single‐item instruments . Hospital‐based physicians have represented a rapidly expanding segment of the internist workforce for more than a decade, but studies of the impact of inpatient vs outpatient practice location on burnout and career satisfaction are limited.…”
mentioning
confidence: 99%
“…Hospital‐based physicians have represented a rapidly expanding segment of the internist workforce for more than a decade, but studies of the impact of inpatient vs outpatient practice location on burnout and career satisfaction are limited. A meta‐analysis of the impact of practice location on burnout relied almost exclusively on noncomparative studies from outside the United States . A recent study of US physician burnout and satisfaction with work‐life balance showed that general internists expressed below average satisfaction with work‐life balance and had the second highest rate of burnout among 24 specialties .…”
mentioning
confidence: 99%
“…However, increasing concerns of physician burnout are emerging. [1][2][3][4] It would be valuable to be able to identify trainees at early stages of their careers to help them prepare for successful careers in hospital medicine. Our study looked to identify correlative factors among medical students who report interest in hospital medicine.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In spite of this, hospitalists do report satisfaction with their work-life balance. 4 Medical student specialty choice is a complex issue, and one that has been studied extensively. However, factors that influence why students pursue hospital medicine as a career are less well studied.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have mostly been survey studies with limited response rates that may affect their fi ndings. [11][12][13][14] Future studies addressing this important issue may seek to focus on those who plan for hospital medicine to be a long-term career rather than all of those who are currently employed in the profession. Likely such studies will be more germane to these physicians, and response rates among this segment of the hospitalist workforce may be higher.…”
Section: Table 2 Proportion Of Those Who Intended Their First Job To mentioning
confidence: 99%